2019
DOI: 10.1177/0003702818823239
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Infrared Polarization Spectroscopy Measurements of Species Concentrations and Temperature in a Low-Pressure Flame

Abstract: We demonstrate quantitative measurements of methane (CH 4 ) mole fractions in a low-pressure fuel-rich premixed dimethyl ether/oxygen/argon flat flame (Φ = 1.87, 37 mbar) using mid-infrared (IR) polarization spectroscopy (IRPS). Non-intrusive in situ detection of CH 4 , acetylene (C 2 H 2 ), and ethane (C 2 H 6 ) in the flame was realized by probing the fundamental asymmetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Comparing Eqs. (15) and (16), the PS signal is only dependent on the probe beam intensity under the saturating conditions. In many cases, the saturating conditions are usually selected to perform the experiments because of the low effect of intensity fluctuations and high signal intensity when using high pump energy.…”
Section: Numerical Analysis Of Irps Signalsmentioning
confidence: 99%
See 3 more Smart Citations
“…Comparing Eqs. (15) and (16), the PS signal is only dependent on the probe beam intensity under the saturating conditions. In many cases, the saturating conditions are usually selected to perform the experiments because of the low effect of intensity fluctuations and high signal intensity when using high pump energy.…”
Section: Numerical Analysis Of Irps Signalsmentioning
confidence: 99%
“…Their experimental results showed a good agreement with the simulation spectra. More recently, by probing the C-H asymmetric stretching in the spectral range of 2970-3340 cm −1 , Sahlberg et al [16] demonstrated the non-intrusive detection of C 2 H 6 , C 2 H 2 , and CH 4 in the low-pressure flame. The collision effects on the IRPS signal were reported at sub-atmospheric pressure of 37 mbar.…”
Section: Quantitative Detection Of Species and Temperature Using Irpsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Figure 4 and Table 7, the wavenumber of 3343 cm −1 was an -OH stretching vibration [24]. A wavenumber of 1724 cm −1 was the characteristic absorption peak of C=O [25], while wavenumber 1530 cm −1 was the N-H bending vibration of the amide II band [26], indicating that there were a large number of carbamate bonds in the product.…”
Section: Chemical Composition Of the Waterborne Uv/al Low Infrared Emissivity Coatingmentioning
confidence: 99%